Season of shattered dreams : postwar baseball, the Spokane Indians, and a tragic bus crash that changed everything - Vickrey, Eric, 1979- (Rowman & Littlefield, 2024)
"In 1946, a bus carrying the Spokane Indians baseball team crashed, leaving nine players dead and six hospitalized. This book tells their stories, primarily through the lives of three key players, following them through WWII, into the 1946 season that was greatly impacted by men returning from overseas, and through the crash that changed everything"--